Transport Policy, Acceptance and the Media - Bernhard Wieland; Tina Seidel; Andreas Matthes; Bernhard Schlag (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 2004)
The last two decades have seen a substantial change in the basic philosophy underlying European transportation policy. Due to the Commission's efforts and due to supporting jurisdiction by the European Court of Justice the dominant approach to transportation policy has become far more market oriented. This change of approach in transportation policy will only be successful and sustainable if the problem of acceptability will be solved. For researchers this entails that their perspective must change from the normative to the positive aspects of transportation policy-making. This paper reports work undertaken within research project TIPP (Transportation Institutions in the Policy Process) funded by the European Commission. In this work it has been attempted to develop a theoretical structure that merges the positive economic theory of regulation with cognitive psychology and traffic psychology. This theoretical structure offers a matrix of actors and factors that are seen to be essential for success or failure in the implementation of a certain measure of transport policy. Four case studies were carried out in order to check the plausibility of this approach. The case studies are the failure of the German Railway (Deutsche Bahn AG) to introduce a new tariff system in passenger transport in the period 2002-2003, the attempt to introduce a toll for HGVs in Germany, the failure to operate a private tolled motorway in Hungary (M1/M15), the failure to introduce a road-pricing system in the densely populated Randstad area in the Netherlands.
Keywords: L91; L9; L51; L98; 330; Transportation Policy; Europe; Common Transport Policy; Transport Regulation; Acceptability; EU-Verkehrspolitik; Verkehrspolitik; Deregulierung; Öffentliche Meinung; Kognition; EU-Staaten